Neurogenic tremor through TRE Tension, Stress and Trauma Releasing Exercises according to D. Berceli in the treatment of post-traumatic stress disorder PTSD (russian) - Герольд, Андреас (Psychological Counseling and Psychotherapy)
Tension, Stress und Trauma Releasing Exercises (TRE) are a sequence of seven exercises used to trigger neurogenic tremor. The aim of this tremor is to reduce symptoms of post-traumatic stress disorder PTSD and other stress-induced symptoms. This article describes the basic features of PTSD, the TRE method, the scientific explanatory model, the principle behind the exercises and the main features of self-regulation.